2014
DOI: 10.4172/2165-7939.1000185
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Sacroiliac Joint Arthrodesis: Experience in a Prospective Series with 24 Patients

Abstract: Background: Sacroiliac (SI) joint pain conservative treatments show poor outcomes. Hypothesis: surgical treatment will show better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
3
28
1
Order By: Relevance
“…The improvements in quality of life seen in our study mirror those seen in a prior randomized trial [43]. Our study, combined with the prior randomized trial and 4-and 5-year outcomes from both European [39] and US [45] cohorts, suggest that minimally invasive SIJ fusion can be added to the portfolio of spine surgeries proven safe and effective that European surgeons can offer their patients.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The improvements in quality of life seen in our study mirror those seen in a prior randomized trial [43]. Our study, combined with the prior randomized trial and 4-and 5-year outcomes from both European [39] and US [45] cohorts, suggest that minimally invasive SIJ fusion can be added to the portfolio of spine surgeries proven safe and effective that European surgeons can offer their patients.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings both replicate and extend previous studies. In previously published case series [36][37][38][39], systematic reviews [40,41], a prospective multicenter clinical trial [42], and a recently published randomized clinical trial of similar design conducted in the USA [43], similar improvements in SIJ pain, self-rated limitations in activities due to pain (Oswestry Disability Index) and quality of life were observed in participants undergoing SIJF. Our study provides an additional, independent confirmation that the improvements after surgery are clinically important and statistically superior to those seen with continued conservative care.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Minimally invasive fusion of the SIJ has been performed with several types of implants, including triangular, porous, titanium coated implants, 19,[27][28][29][30][31][32][33] hollow modular screws, [34][35][36] titanium cages, 37,38 and allograft dowels 21 ( Table 2). Minimally invasive fusion aims to permanently stabilize the SIJ but avoid the morbidity of the open procedure.…”
Section: Coverage Rationale For Open and Minimally Invasive Sij Fusionmentioning
confidence: 99%
“…26 Finally, two published studies report that favorable outcomes achieved at one year are sustained long term (up to 5 years). 30,33 The complication rate for minimally invasive SIJ fusion with triangular titanium implants is low. 50 Revision rates over 4 years (3.5% 47 ) are substantially lower than after lumbar fusion surgery, and revision rates in long-term retrospective 30,33 and prospective studies 19,31 have confirmed this low rate.…”
Section: Coverage Rationale For Open and Minimally Invasive Sij Fusionmentioning
confidence: 99%